Casta y raza en la Cuba de mitad del siglo xix - Amparo Sánchez Cobos (Caravelle)
This paper analyses the spanish reformer Ramón de la Sagra’s opinion about Cuban society concerning its division into races and castes in the middle of the 19th century, a notion that is largely represented in the texts he wrote about slavery in the island. Through this, this article aims to demonstrate up to what point this author reproduced the typical racial theories of his time and how he perceived the colonial society.Cuba, 19th century, Caste, Race, Ramón de la Sagra